Who is At -risk of Homelessness?Enumerating and Profiling the Population to Inform Prevention. - Batterham, Deborah (My University, 2021)
While much international research has focused on enumerating and profiling populations experiencing homelessness, the same cannot be said for those at-risk of homelessness. Yet in order to successfully prevent homelessness we must first know who is at-risk and why. This paper uses two panel surveys to operationalise and test a definition of homelessness risk and subsequently enumerate and profile the population at-risk of homelessness in Australia. Findings revealed that 7.9% of people aged 15 years and over, just under 1.5 million people, were at-risk of homelessness in Australia in 2015. Compared with the national population, those at-risk are more likely to be women, to be Indigenous and to report fair or poor health. They also have lower levels of educational attainment and are more likely to be on low incomes and in receipt of income-support payments, linking risk of homelessness with multiple indicators of poverty and disadvantage. The paper concludes by discussing opportunities for future international scholarship on homelessness risk using household panel surveys and draws on the findings to suggest directions for primary prevention efforts in Australia.
European Journal of Homelessness
Keywords: Disadvantage, adversity and resilience; Housing, communities and neighbourhoods